Instructional evaluation and accountability (2009)
This paper is necessitated by the need to introduce student educators to rudiments of instructional evaluation and accountability in the context of the Nigerian education system in the twenty-first century. It is also meant to equip them for the challenges posed by educational evaluation and accountability in order to assist them to position themselves in such a way that always be able to evaluate the level of attainment of instructional objectives of any instructional strategy as well as to determine how accountable or responsible such a strategy is for the attainment of stated behavioural or learning objectives. The paper highlights the relationships among the three key words in the title of the paper: instruction, evaluation and accountability and how they operate separatly and together for the achievement of the state objectives. The interdependence of evaluation and accountability in bringing about improved instructional and the subsequent realization of learning outcomes is stressed.